2020
DOI: 10.1007/s10694-020-00993-z
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of the UK’s Regulatory Regime for Combustible Façades

Abstract: proportionately large number of vertical and horizontal cavity barriers of a higher specification than required by statutory guidance. These aids to meeting the criteria are not proscribed by BS 8414-1 but are not commonly found in actual rainscreen system designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…no. 123694, https://doi.org/10.1016/j.jhazmat.2020.123694 2 standard, the BR 135 criteria, and the DCLG tests has been reported elsewhere 5 . Three combustible insulation products were reported to have met these criteria, two phenolic foams and one PIR foam.…”
Section: Introductionmentioning
confidence: 92%
“…no. 123694, https://doi.org/10.1016/j.jhazmat.2020.123694 2 standard, the BR 135 criteria, and the DCLG tests has been reported elsewhere 5 . Three combustible insulation products were reported to have met these criteria, two phenolic foams and one PIR foam.…”
Section: Introductionmentioning
confidence: 92%
“…There has been consistent rectification of the relevant building regulations in various jurisdiction worldwide. [95][96][97][98] In the Australian context, the Lacrosse Building fire and the Grenfell Tower Fire have highlighted the need for regulatory reforms regarding flammable cladding material. Concerns have also been raised about other potentially flammable building materials.…”
Section: Current Cladding Regulations and Taskforcesmentioning
confidence: 99%
“…BS 8414-1 is well-recognized in UK, China, Japan, and the United Arab Emirates. 98 The test façade is configured according to the dimensions above with an expected heat output for the crib of 4500 MJ over 30 minutes to achieve the following exposure: (c) failure due to internal fire spread is determined when any internal thermocouple at level 2 exceeds 600 C above ambient for a period of at least 30 seconds, within 15 minutes of the fire spread start time.…”
Section: Full Scale Façade Tests-bs8414-1mentioning
confidence: 99%
“…In 2018, the Department for Communities and Local Government (DCLG) (now the Ministry of Housing and Local Government (MHCLG)) commissioned a series of BS 8414-1 tests on a set of building façades in the burn hall at BRE in the UK. The test construction was described in the reports and was not representative of typical building design and practice [8]. Of these tests, three involved the same combinations of ACM and insulation materials as our tests: PIR/PE [18], PIR/A2 [19] and SW/A2 [20].…”
Section: Comparison To Other Testsmentioning
confidence: 99%
“…These test results indicated that the use of ACM-A2 ensured the fire safety of tall buildings covered in combustible insulation, since they met the AD B criteria. A critique of the BS 8414 standard, the BR 135 criteria, the DCLG tests, and differences between facades constructed for fire tests and normal building industry practice has been reported elsewhere [8]. The aim of this work was to provide experimental data to inform the fire safety strategy for tall buildings.…”
Section: Introductionmentioning
confidence: 99%